Computer-aided in choosing education programs (CASCEP) - Mohd, Fatihah; Mohamad Noor, N.M.; Yusof, Yuhanif (Medwell Journal, 2009)
Computer-Aided Decision Making (CADM) has been widely used in various decision contexts. This study is focused on CADM for Choosing Education Programs (CASCEP) to rank the performance of a set of decision alternative with respect to multiple criteria. CASCEP has been developed in Visual Basic (VB) that will select and rank the programs that are more suitable to the Malaysian Certificate of Education (SPM) leavers based on 2 inter-related factors: the student's SPM results and minimum programs requirements. In this prototype, 5 programs are offered by Universiti Teknologi Malaysia (UTM) have been selected as a sample programs. Rule-based reasoning technique is used as an engine in order to search the most suitable education program. In this engine, score or value of each program is generated to rank the programs.